Rancang Bangun Sistem Presisi Manuvering pada Pergerakan Kapal - Muhamad Ghali Pw Carwito; Antonius Edy Kristiyono; Henna Nurdiansari (Lembaga Pengembangan Kinerja Dosen, 2025)
In recent decades, the use of unmanned vehicles (UV) has increased significantly. Unmanned ship operations involve various technical challenges that require sophisticated solutions. Dynamic marine environments, including strong currents, high waves, and extreme weather conditions, can affect ship performance to maintain stability and steer the ship properly, a precise and responsive control system is essential. Small errors in maneuvering can result in high risks, such as damage to the ship or loss of cargo, as well as potential danger to other ships or the environment. The purpose of this study is to design and build a servo motor control system for maneuvering systems on ships and to determine whether servo motors can control maneuvering systems on unmanned ships. The results of this study indicate that the servo motor control system in this study can work automatically or manually. In automatic mode, the motor angle can be set via the application. The ship will stop when the angle matches the settings in the application, based on data from the compass sensor. This sensor ensures that the direction of the ship's movement is accurate by providing a signal when the angle set matches the compass angle. The angle that has been determined when maneuvering the ship's automatic movement system is not accurate, due to currents, water waves and wind that make the ship move or change position by itself.